-13-n=-7+-7n

Simple and best practice solution for -13-n=-7+-7n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13-n=-7+-7n equation:


Simplifying
-13 + -1n = -7 + -7n

Solving
-13 + -1n = -7 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
-13 + -1n + 7n = -7 + -7n + 7n

Combine like terms: -1n + 7n = 6n
-13 + 6n = -7 + -7n + 7n

Combine like terms: -7n + 7n = 0
-13 + 6n = -7 + 0
-13 + 6n = -7

Add '13' to each side of the equation.
-13 + 13 + 6n = -7 + 13

Combine like terms: -13 + 13 = 0
0 + 6n = -7 + 13
6n = -7 + 13

Combine like terms: -7 + 13 = 6
6n = 6

Divide each side by '6'.
n = 1

Simplifying
n = 1

See similar equations:

| -36x^2+66xy-28y^2= | | .14-25.12=3.14 | | 0.5=1.2x+1.4 | | 3m-5=5m+6-m | | 13-(5b)= | | 3/4g-9=4(g+1) | | 3.14-25.14=3.14 | | 3x-8=-5-32 | | 5(x+1)=7(2x-x) | | 20+7p=2p+5 | | 7S+9(9S+80)= | | 9x^2+8y^2=72 | | 24-2[(5-2)(14-12)+3]= | | -111-5a=6(5a+4) | | y-4=3x-15 | | 3.14-5.12=3.1 | | 3a-12a+2a=3a+14 | | G=v(b+1) | | -2(5x+8)=3x-23 | | -3(-4Z+-5)= | | x=45+12x | | (2a+3)(3a-4)= | | 9=4+5x | | 75-x=x+5 | | 0.25+2x=360 | | 5y+9-y=26 | | 0.9(7x+4)=0.7-(x-3) | | 10t-6-t=9t-6 | | -10+10+-5B*2+-1+-5B= | | 4x-2+x=-2+2 | | 3(3x-8)=4x-6 | | 51x+18-29x=131 |

Equations solver categories